2020
DOI: 10.1108/ijm-07-2019-0347
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the green behaviour of academics

Abstract: Purpose Studies have highlighted concerns about the role of knowledge creation between human resource management practices and employee behaviour. The purpose of this paper is to examine the impact of green human resource management (green HRM) on employee green behaviour (EGB) through the mediation of environmental knowledge of lecturers in public research universities in Malaysia. Design/methodology/approach This cross-sectional study examines the mechanism in which green HRM affects the EGB of lecturers t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
100
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 178 publications
(147 citation statements)
references
References 83 publications
(164 reference statements)
6
100
2
Order By: Relevance
“…Several theories were used to explain EGB, such as the theory of planned behavior (TPB; Blok et al, 2014;Safari et al, 2018;Wesselink et al, 2017), value-belief-norms theory (VBN; Tezel & Giritli, 2019;Vanderploeg & Lee, 2019;Yeboah & Kaplowitz, 2016), norm activation model (NAM; Banwo & Du, 2019;Fang et al, 2019), values-identity-personal norms (VIP; Ruepert et al, 2016Ruepert et al, , 2017, and theory of normative conduct (TNA; Norton et al, 2014). In some studies, the theories used were social exchange theory (Fatoki, 2019;Gkorezis & Petridou, 2017;Hameed et al, 2019), social identity theory (Kim et al, 2019), theory of social learning (Yang, 2019), and technology acceptance model (Zhang et al, 2019), whereas in other studies, the theory used to explain EGB was the abilitymotivation-opportunity theory (AMO; Dumont et al, 2016;Fawehinmi et al, 2020;Saeed et al, 2019). However, the use of a mixture of different theories to explain EGB was seen only in a few studies.…”
Section: Need For the Studymentioning
confidence: 99%
See 3 more Smart Citations
“…Several theories were used to explain EGB, such as the theory of planned behavior (TPB; Blok et al, 2014;Safari et al, 2018;Wesselink et al, 2017), value-belief-norms theory (VBN; Tezel & Giritli, 2019;Vanderploeg & Lee, 2019;Yeboah & Kaplowitz, 2016), norm activation model (NAM; Banwo & Du, 2019;Fang et al, 2019), values-identity-personal norms (VIP; Ruepert et al, 2016Ruepert et al, , 2017, and theory of normative conduct (TNA; Norton et al, 2014). In some studies, the theories used were social exchange theory (Fatoki, 2019;Gkorezis & Petridou, 2017;Hameed et al, 2019), social identity theory (Kim et al, 2019), theory of social learning (Yang, 2019), and technology acceptance model (Zhang et al, 2019), whereas in other studies, the theory used to explain EGB was the abilitymotivation-opportunity theory (AMO; Dumont et al, 2016;Fawehinmi et al, 2020;Saeed et al, 2019). However, the use of a mixture of different theories to explain EGB was seen only in a few studies.…”
Section: Need For the Studymentioning
confidence: 99%
“…When green HRM practices as highlighted above are experienced by the employees, they tend to be psychologically prepared for and inclined toward the practicing of EGB (Fawehinmi et al, 2020). Studies have shown green HRM affects the environmental commitment of employees (Pham et al, 2020), and such commitment would lead to the performance of EGB.…”
Section: Green Hrm and Egbmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, climate change is considered one of the major green environmental problems, posing great threats to human kind. International organizations, countries around the world, and companies have all realized the importance of protecting the environment (Ansari et al, 2020;Fawehinmi et al, 2020;Hameed et al, 2020;Harris et al, 2017;Ogbeibu et al, 2020;Pham, Hoang, & Phan, 2019;Pham et al, 2020;Raut et al, 2020;Ren et al, 2018Ren et al, , 2020Shahriari & Hassanpoor, 2019;Song et al, 2020). The 2015 United Nations Climate Change Conference reached the Paris consensus and, according to the agreement, it aims to strengthen the global response to the threat of climate change, to hold the global average temperature rise to no more than 2°C compared with preindustrial times, and to strive to control the temperature rise within 1.5°C.…”
Section: Introductionmentioning
confidence: 99%